PENGARUH KUALITAS SISTEM, KUALITAS INFORMASI, DAN KUALITAS LAYANAN TERHADAP KEPUASAN PENGGUNA SISTEM INFORMASI AKUNTANSI - Muhammad Fathurrahman (2023)
This study aims to examine the effect of system quality, information quality, and service quality on accounting information system user satisfaction. In the information system success model by DeLone and McLean (2003) said that there are variables that affect user satisfaction, namely the variables of System Quality, Information Quality and Service Quality. The research population is restaurants, cafes and culinary places in the Bekasi area. The sample in this study are cashier application users in restaurants, cafes and culinary places using the accidental sampling method. The results of this study are that system quality and information quality have no significant effect on user satisfaction, while service quality has a significant effect on accounting information system user satisfaction. These results mean that even though the quality of the system and the quality of the information is good and adequate, it does not necessarily affect user satisfaction. Meanwhile, users need more and focus on the quality of services provided.